Effects of oncoming target velocities on rapid force production and accuracy of force production intensity and timing. Issue 23 (2nd December 2017) - Ohta, Yoichi
ABSTRACT: The present study aimed to clarify the effects of oncoming target velocities on the ability of rapid force production and accuracy and variability of simultaneous control of both force production intensity and timing. Twenty male participants (age: 21.0 ± 1.4 years) performed rapid gripping with a handgrip dynamometer to coincide with the arrival of an oncoming target by using a horizontal electronic trackway. The oncoming target velocities were 4, 8, and 12 m · s −1, which were randomly produced. The grip force required was 30% of the maximal voluntary contraction. Although the peak force (Pf) and rate of force development (RFD) increased with increasing target velocity, the value of the RFD to Pf ratio was constant across the 3 target velocities. The accuracy of both force production intensity and timing decreased at higher target velocities. Moreover, the intrapersonal variability in temporal parameters was lower in the fast target velocity condition, but constant variability in 3 target velocities was observed in force intensity parameters. These results suggest that oncoming target velocity does not intrinsically affect the ability for rapid force production. However, the oncoming target velocity affects accuracy and variability of force production intensity and timing during rapid force production.